A experiência da velhice à flor da pele: o gesto da dança como formação do sujeito velho - Zucco, Amanda Khalil Suleiman (My University, 2022)
This study proposes to investigate the concepts of body, in the phenomenology of Merleau- Ponty, and experience, in the hermeneutics of Gadamer, with the purpose of analysing their contributions to the aesthetic experience of the danced gesture as formation of the person in the old age. In Merleau-Ponty, the notion of body-object is broken and one understands the body as an interlaced presence in the world, and the existence is corporal, in other words, the body is seen as a possibility of contact from the experience, this being a condition for the formation of the old person. In Gadamer, one deviates from the modern conception of experience and one is guided from the hermeneutical experience, with a view to the process of formation and, specially to the aesthetic experience of the danced gesture in the old age. The development of this research was oriented by a theoretical-conceptual investigation about the philosophical thoughts and some selected works by Maurice Merleau-Ponty (1908-1961) and Hans-Georg Gadamer (1900-2002). The investigative movements are made from the analysis, description and interpretation of the structuring concepts, in order to clarify them for the establishment of dialogues with the study theme. Thus, this dissertation is organized in three chapters. The first one, entitled "Body and old age in displacement: en route to the corporeality in Merleau-Ponty", presents a displacement of the body-awareness conception and it is oriented by the corporeality apprehension in Merleau-Ponty, in order to discuss the body in the old age. Right after, the second chapter, "The experience and the old age: in search of the aesthetic experience in Gadamer", that proposes the approach of the hermeneutical experience in Gadamer to the old age, with a view to pursue the aesthetic experience from the existence concept. In the third chapter, "The gesture of the dance and the formation in the experience of the old age: a horizon of senses", the danced gesture is presented as a possibility of aesthetic experience of the artist in the old age, in other words, as formation of the person. [resumo fornecido pelo autor]
O presente estudo propõe-se a investigar os conceitos de corpo na fenomenologia de Merleau- Ponty e experiência na hermenêutica de Gadamer, a fim de analisar suas contribuições para a experiência estética do gesto dançado como formação do sujeito na velhice. Em Merleau-Ponty rompe-se a noção do corpo-objeto e compreende-se o corpo como presença entrelaçada no mundo, sendo que a existência é corporal, ou seja, o corpo como possibilidade de contato a partir da experiência, sendo assim, condição para a formação do sujeito velho. Em Gadamer, afasta-se da concepção moderna de experiência e orienta-se a partir da experiência hermenêutica com vistas ao processo de formação, e, especialmente para a experiência estética do gesto dançado na velhice. O desenvolvimento desta pesquisa orientou-se por uma investigação teórica-conceitual sobre os pensamentos filosóficos e algumas obras selecionadas de Maurice Merleau-Ponty (1908-1961) e Hans-Georg Gadamer (1900-2002). Os movimentos investigativos se fazem a partir da análise, descrição e interpretação dos conceitos estruturantes de modo a elucidá-los e estabelecer diálogos com a temática do estudo. Assim, a presente dissertação está organizada em três capítulos. O primeiro, intitulado "Corpo e velhice em deslocamento: a caminho da corporeidade em Merleau-Ponty" apresenta um deslocamento da concepção de corpo-consciência e passa a orientar-se pela compreensão corporeidade em Merleau-Ponty, a fim de discutir o corpo na velhice. Logo após, o segundo capítulo "A experiência e a velhice: em busca da experiência estética em Gadamer" propõe a aproximação da experiência hermenêutica em Gadamer com a velhice, tendo em vista perseguir a experiência estética a partir do conceito de vivência. E, por fim, o terceiro capítulo "O gesto da dança e a formação na experiência da velhice: um horizonte de sentidos", apresenta o gesto dançado como possibilidade de experiência estética do artista na velhice, isto é, como formação do sujeito. [resumo fornecido pelo autor]
Keywords: Envelhecimento - Educação; Idosos - Educação; Educação; Merleau-Ponty, Maurice, 1908-1961; Gadamer, Hans-Georg, 1900-2002; Aging - Education; Older people - Education; Education